2020
DOI: 10.7759/cureus.8723
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Brothers: Familial Voltage-Gated Potassium Channel Autoimmune Encephalitis

Abstract: This is the first reported case of familial voltage-gated potassium channel (VGKC) autoimmune encephalitis. The symptoms of autoimmune encephalitis can mimic infectious encephalitis with headache, fatigue, and neuropsychiatric symptoms. Autoimmunity is emerging as a distinct cause of encephalitis in the children. Prompt recognition, diagnosis, and treatment are important to prevent brain damage. Two brothers presented two years apart with different symptoms. The explanation for their distinct symptoms lies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Leucine-rich glioma-inactivated protein 1 (LGI-1), contactin-associated protein-like 2 (CASPR-2), or seronegative subtype. Both LGI-1 and CASPR-2 are found within the VGKC protein complex [ 8 , 9 ]. In our case, both LGI-1 and CASPR-2 antibodies were found to be negative; however, VGKC protein complex antibody levels were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine-rich glioma-inactivated protein 1 (LGI-1), contactin-associated protein-like 2 (CASPR-2), or seronegative subtype. Both LGI-1 and CASPR-2 are found within the VGKC protein complex [ 8 , 9 ]. In our case, both LGI-1 and CASPR-2 antibodies were found to be negative; however, VGKC protein complex antibody levels were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that after viral infection in the CNS, some patients develop parainfectious AE. [8][9][10][11] AE occurs in 27% of patients. [12] In this case, the patient first showed signs of herpesvirus encephalitis, was later found to have a positive CASPR2 antibody, and was subsequently considered to have an infection due to AE.…”
Section: Discussionmentioning
confidence: 99%
“…To date, almost all reported cases of autoimmune encephalitis were sporadic cases except for one familial autoimmune encephalitis reported in two pediatric brothers affected with voltage-gated potassium channel (VGKC) encephalitis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%